Screening for the C9ORF72 expansion in Greek Huntington Disease phenocopies and controls and meta-analysis of current data. (12th June 2020) - Rikos, Dimitrios; Marogianni, Chrysoula; Provatas, Antonios; Bourinaris, Thomas; Arnaoutoglou, Marianthi; Stathis, Pantelis; Patrinos, George P.; Dardiotis, Efthimios; Hadjigeorgiou, George M.; Xiromerisiou, Georgia
Background: Several European studies examined the role of C9orf72 repeat expansion in patients with Huntington-disease like phenotypes (HD-L). The scope of our study is to investigate the expansion frequency in a Greek HD-L cohort and the meta-analysis of all published cases. This will be of use in genetic counseling of these cases. Methods: A cohort of 74 patients with HD-L and 67 healthy controls were screened for the C9orf72 expansion status. Case-controls comparison was assessed with the Pearson's chi-square statistic for a 2 × 2 table. A systematic database search was conducted and seven studies, including the current study, were considered eligible for inclusion in a meta-analysis considering a total of 812 patients with HD phenocopies. Pooled mutation frequency was calculated using a Random Effects model or the Mantel-Haezsel fixed effects model, depending on the observed heterogeneity. Results: In our cohort, one patient was found to have a pathologic expansion of C9orf72, and none from the control group (chi-square: 0.91, p-value: 0.34). Pooled mutation frequency was found at 2% (CI: 1–3%) with low heterogeneity (I 2 :15%). Discussion: Based on this meta-analysis the recommendation for genetic testing for C9orf72 expansions is further solidified.